2012
DOI: 10.1021/la301228j
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectricity: Macroscopic Charge Patterns Formed by Self-Arraying Ions on Polymer Surfaces

Abstract: Tribocharged polymers display macroscopically patterned positive and negative domains, verifying the fractal geometry of electrostatic mosaics previously detected by electric probe microscopy. Excess charge on contacting polyethylene (PE) and polytetrafluoroethylene (PTFE) follows the triboelectric series but with one caveat: net charge is the arithmetic sum of patterned positive and negative charges, as opposed to the usual assumption of uniform but opposite signal charging on each surface. Extraction with n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
124
0
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 56 publications
9
124
0
10
Order By: Relevance
“…Charged domains were detected by scanning the polymer surfaces with a macroscopic Kelvin electrode. 7 This finding has no precedents in the literature, but it converges with previous results on charge nanopatterning in dielectric surfaces, confirming that the charge distribution on these surfaces follows fractal behavior. …”
supporting
confidence: 89%
See 3 more Smart Citations
“…Charged domains were detected by scanning the polymer surfaces with a macroscopic Kelvin electrode. 7 This finding has no precedents in the literature, but it converges with previous results on charge nanopatterning in dielectric surfaces, confirming that the charge distribution on these surfaces follows fractal behavior. …”
supporting
confidence: 89%
“…7,14 Surprisingly, the potential patterns obtained after rubbing PTFE with PE foam disks immersed in ethanol and dried for different times showed only negative potentials when the PE disks were dried only for short times (Figures 1a, 1b, and 1c). Positive domains (Figure 1d) also appeared, but only after longer drying times (1050 s), when ethanol evaporation was complete, as verified by weighing the PE samples to within «0.01 mg (allowing detection of 1% of the total amount of absorbed ethanol).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…1 Later studies indicated that friction/rubbing is not a necessary condition to generate charges on contacting surfaces. 2 We still do not fully understand how and why such charge generation occurs, 3,4 although considerable progress has been made, such as by considering the role of mechanochemistry 6,7 and the difference of the composite between the surface and the bulk, 2,4,5,8 to more closely reveal the CE charging mechanism. Many researchers have suggested that moisture adsorbed on the surface plays a role in CE 9 and the related ambient humidity is also thought to be particularly important for surface charging.…”
Section: Introductionmentioning
confidence: 99%